Heavy metals assessment for sustainable management in Estuaries of Ba Ria-Vung Tau Province - Hung Phu, Le; Hong Ngoc, Pham; Trong Dung, Le; Hong Thu, Nguyen; Van The, Ho; Tuan Linh, Vo Tran; Minh Hieu, Nguyen; Minh Thu, Phan (Vietnam Journal of Marine Science and Technology, 2024)
Heavy metal concentration in the aquatic environment of estuaries is a significant environmental concern with potential consequences for ecosystems and human health. Heavy metals are naturally occurring elements that can enter aquatic environments through both natural processes and human activities. The interplay between natural processes and human activities, particularly urbanization and industrialization, often exacerbates heavy metal pollution in aquatic ecosystems. Some of the most common heavy metals of concern in estuarine pollution include arsenic (As), cadmium (Cd), mercury (Hg), lead (Pb), zinc (Zn), and iron (Fe). Based on the results of two surveys in rainy and dry seasons, the paper aims to assess the concentrations of heavy metals in the estuarine environment of Ba Ria - Vung Tau Province, Vietnam, to understand the extent of contamination and its potential impacts on the ecosystem and human health. The average concentrations As, Cd, Hg, Pb, Zn, and Fe were 2.01, 0.024, 0.028, 1.63, 4.71, and 492.9 µg/L in water, and 6.70, 0.175, 0.060, 11.78, 41.94, and 3,108.9 mg/kg in sediment, respectively. Heavy metal concentrations in water have an increased trend during the rainy season. In contrast, values in sediment exhibit an opposite pattern, which can be explained by various environmental factors and processes. For water and sediment quality, individual metals, and overall metal contamination levels (the contamination factor - Cf, contamination degree - Cd, and metal pollution index - MPI) may appear to be low, whereas the assessment of the combined effects of multiple metals (Metal quality index - MI > 1) indicates that there is a potential risk to aquatic life in the estuaries. This assessment may underscore the importance of considering not only individual metal concentrations but also their cumulative effects when evaluating water and sediment quality and making decisions regarding protecting aquatic ecosystems. Further investigations and measures may be needed to mitigate potential harm to aquatic organisms and for sustainable management in estuaries.